Influence of Antibiotic Promotion Practices on Pharmacovigilance and Resistance Reporting Patterns - Suraj Sen; Anit Jha; Rajeev Ratan; Deepak; Nitesh Kumar; Azad (International Journal of Antibiotics, 2026)
The global escalation of antimicrobial resistance (AMR) has emerged as a critical public health crisis, undermining decades of therapeutic advancements. While inappropriate prescribing and misuse of antibiotics are widely acknowledged contributors, the role of pharmaceutical promotion practices remains underexplored in influencing prescribing behaviors and downstream pharmacovigilance systems. This review critically examines how antibiotic promotion strategies – ranging from direct physician engagement to digital marketing – affect adverse drug reaction (ADR) reporting and resistance surveillance patterns. The article integrates insights from pharmacovigilance frameworks, antimicrobial stewardship programs, and healthcare marketing ethics to evaluate the multidimensional impact of promotional activities. Evidence suggests that aggressive marketing may skew prescription trends toward newer, broad-spectrum antibiotics, potentially leading to underreporting of ADRs and delayed resistance detection. Furthermore, promotional bias may influence clinicians’ perception of drug safety, thereby affecting spontaneous reporting systems. This review also highlights systemic gaps in pharmacovigilance reporting, particularly in low- and middle-income countries, where regulatory oversight is limited and promotional influence is often stronger. Mechanistic pathways linking promotion practices to resistance reporting distortions are discussed, including cognitive bias, selective information dissemination, and economic incentives. The study concludes by emphasizing the need for stricter regulatory frameworks, enhanced transparency in pharmaceutical marketing, and integration of pharmacovigilance with antimicrobial stewardship initiatives. Strengthening these systems is essential to ensure rational antibiotic use and accurate resistance monitoring, ultimately safeguarding global health.
Keywords: Antibiotic promotion; adverse drug reaction reporting; antimicrobial resistance; antimicrobial stewardship; drug safety surveillance; pharmaceutical marketing; pharmacovigilance